2016
DOI: 10.4103/0259-1162.186620
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of ultrasound guided transversus abdominis plane block versus local anesthetic infiltration in adult patients undergoing single incision laparoscopic cholecystectomy: A randomized controlled trial

Abstract: Background:Transversus abdominis plane (TAP) block has been used to provide intra- and post-operative analgesia with single incision laparoscopic (SIL) bariatric and gynecological surgery with mixed results. Its efficacy in providing analgesia for SIL cholecystectomy (SILC) via the same approach remains unexplored.Aims:The primary objective of our study was to compare the efficacy of bilateral TAP block with local anesthetic infiltration for perioperative analgesia in patients undergoing SILC.Settings and Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
24
1
Order By: Relevance
“…In another study post-operative morphine consumption and pain scores were assessed after giving TAP block or port-site infiltration after single-incision laparoscopic cholecystectomy. [ 19 ] In contrast to our study, they found that TAP block was not effective in reducing the 24 h morphine consumption even though it provided analgesia in the early post-operative period.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study post-operative morphine consumption and pain scores were assessed after giving TAP block or port-site infiltration after single-incision laparoscopic cholecystectomy. [ 19 ] In contrast to our study, they found that TAP block was not effective in reducing the 24 h morphine consumption even though it provided analgesia in the early post-operative period.…”
Section: Discussioncontrasting
confidence: 99%
“…For the primary outcome of pain control at rest and during coughing, out of 23 studies, 22 studies were included in the analysis for which references have been provided in Table 3 . Some of the included studies had reported data only for one or two timepoints for post-operative pain score either for 0 or 6 or 12 or 24 h at rest or during coughing ( 17 , 18 , 20 , 22 24 , 26 , 28 , 30 , 36 38 ). A single study by El-Dawlatly et al ( 27 ) only provided the data for morphine consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have compared ultrasound-guided TAP block with trocar site local anesthetic infiltration. The results varied from significant reduction [33] to non-significant reduction [34] in cumulative morphine use at 24 h with TAP blocks compared with local anesthetic infiltration. A recent trial [35] has reported that ultrasound-guided TAP block has no significant clinical benefit over trocar site local anesthetic infiltration in laparoscopic nephrectomy.…”
Section: Discussionmentioning
confidence: 99%